Navigating Legal Boundaries: Academic Freedom and Content Restrictions in Turkish Publication - Katalin, Siska (Nurani Hukum, 2023)
In a MetroPOLL survey conducted in July 2020, 62 percent of Turkish respondents asserted that the media in Turkey lacks freedom, while 50 percent felt inhibited in freely expressing their thoughts on social media due to perceived monitoring and the potential ramifications of their actions. In response to criticism, the government often resorts to accusing critics of terrorist affiliations, posing a threat to the state, or engaging in activities jeopardizing national security. Publicly criticizing the state or government in Turkey carries inherent risks, including facing civil lawsuits, criminal charges, or investigations. Individuals who opt to publish or speak on sensitive subjects or criticize the government may undergo scrutiny, punishment, and legal prosecution, with potential consequences such as job loss and imprisonment. Legal proceedings against those expressing critical opinions have multifaceted negative implications for society, influencing perceptions of freedom of expression and serving as a means to intimidate civil society and stifle dissent. This study focuses on elucidating the primary reasons behind these restrictions and examining prevalent instances of legal action. Moreover, precision in language, avoidance of redundancy, cohesive transitions, quantifying information with specific examples, and the use of neutral language have been employed to enhance the academic tone and clarity of the paragraph.